Site response analysis of liquefiable soil employing continuous wavelet transforms. Issue 1 (13th March 2022) - Chavan, D.; Sitharam, T.G.; Anbazhagan, P.
Abstract : Propagation of the earthquake motion towards the ground surface alters both the acceleration and frequency content of the motion. Acceleration–time record and Fourier amplitude spectrum of the motion reveal changes in the acceleration and frequency content. However, Fourier amplitude spectrum fails to give frequency–time variation. Wavelet transforms overcome this difficulty. In the current study, site response analysis of a liquefiable soil domain has been investigated employing wavelet transforms. Three earthquake motions with distinct predominant frequencies are considered. It is revealed that the moment soil undergoes initial liquefaction, it causes a spike in the acceleration–time history. From the analysis, frequency of the spikes is found to be greater than the predominant frequency of the acceleration time history recorded at the ground surface. Interestingly, the spikes belong to the sharp tips of the shear stress–shear strain curve. Immediately after the spike, acceleration deamplification is observed. Post-liquefaction deamplification (filtering) of the frequency components is also observed.